2001
DOI: 10.1046/j.1523-1755.2001.059002457.x
|View full text |Cite
|
Sign up to set email alerts
|

PAX2 mutations in oligomeganephronia

Abstract: Ocular anomaly and PAX2 mutations should be sought in all patients with OMN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
91
1
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 110 publications
(95 citation statements)
references
References 20 publications
2
91
1
1
Order By: Relevance
“…It is interesting that reevaluation of some patients with the diagnosis of "oligomeganephronia" also showed some PAX2 mutations (10). In this syndrome, nephron structure seemed normal except that glomeruli were reduced in number and were strikingly hypertrophied (10). This report provided one of the first clues that PAX2 mutations cause a pure nephron deficit.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…It is interesting that reevaluation of some patients with the diagnosis of "oligomeganephronia" also showed some PAX2 mutations (10). In this syndrome, nephron structure seemed normal except that glomeruli were reduced in number and were strikingly hypertrophied (10). This report provided one of the first clues that PAX2 mutations cause a pure nephron deficit.…”
mentioning
confidence: 73%
“…PAX2 belongs to the nine-member family of "paired box" transcription factors and is highly expressed in the UB as it undergoes branching morphogenesis (9). It is interesting that reevaluation of some patients with the diagnosis of "oligomeganephronia" also showed some PAX2 mutations (10). In this syndrome, nephron structure seemed normal except that glomeruli were reduced in number and were strikingly hypertrophied (10).…”
mentioning
confidence: 99%
“…3 It has recently been shown to be associated with PAX2 gene mutations as part of the renal-coloboma syndrome. [4][5][6][7] Expression of PAX2 is restricted to cells of astrocytic lineage both during retinal development and in adulthood. Using immunohistochemistry, it has been found that adult retinal cells with the antigenic phenotype present in mature perinatal astrocytes are found only in the region surrounding the optic nerve head, and that astrocyte precursor cells expressing PAX2 are found in a small region surrounding the optic nerve during early development.…”
Section: Aetiologymentioning
confidence: 99%
“…These have been reviewed by Brodsky 11 and include the CHARGE association (coloboma, choanal atresia, congenital heart disease, and multiple other abnormalities), WalkerWarburg syndrome, Goltz focal dermal hypoplasia, Aicardi syndrome, Goldenhar syndrome, and linear sebaceous naevus syndrome. More recently, associations with Dandy Walker malformation 22 and renal coloboma syndrome (with a mutation of PAX2 transcription) [4][5][6][7] have also been described.…”
Section: Associationsmentioning
confidence: 99%
“…In families with the autosomal dominant renal-coloboma syndrome (RCS), more severe renal hypoplasia and ocular colobomas are caused by mutations of a key developmental gene, PAX2 (4). Histopathologic studies of this condition indicate that patients with heterozygous PAX2 mutations have oligomeganephronia-residual nephrons are normally formed and glomeruli exhibit appropriate compensatory hypertrophy, but an absolute nephron deficit causes renal insufficiency (5).…”
mentioning
confidence: 99%